Fairness That Money Can Buy. Procedural Egalitarianism in Practice - Güth, Werner; Kliemt, Hartmut; Justus Liebig University Giessen (My University, 2013)
Contrary to communitarian market criticism institutions relying on money and bidding can strengthen faculties of `self-governance'. Securing procedurally egalitarian bidding on the basis of declared monetary evaluations guarantees that all realized changes of a status quo are in an `objective' (pecuniary) sense equally advantageous for all members of the community. We show how to use this idea in the context of Elinor Ostrom type common(s) projects. Empirical evidence on `procedurally fair bidding' is presented. The practical scope and limits of procedural egalitarianism need further empirical exploration but money may be the best means to express moral values in `communitarian consent'.
Keywords: Fair Procedures; Governing the Commons; Communitarianism; Contractarianism; Egalitarian Mechanisms; Unanimity; ‘Crowding out’; ddc:100; ddc:330